2020
DOI: 10.1038/s41419-020-03184-4
|View full text |Cite
|
Sign up to set email alerts
|

Induction of NEDD8-conjugating enzyme E2 UBE2F by platinum protects lung cancer cells from apoptosis and confers to platinum-insensitivity

Abstract: Platinum is a widely used first-line chemotherapy in treating non-small cell lung cancer of adenocarcinoma. Unfortunately, platinum resistance leads to relapse and therapeutic failure, enabling the development of platinum-sensitization strategies to be of great clinical significance. Here, we report that the upregulation of the NEDD8-conjugating enzyme UBE2F is an important way for lung cancer cells to escape platinum-induced cell apoptosis, which confers to insensitivity to platinum-based chemotherapy. Mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…9 A, the genetic nanomedicine significantly inhibited the Neddylation modification of Cul1 but had little influence on the Neddylation modification of Cul5 in Huh7 cells. This outcome was a result of the role of Cul1 as a ROC1 substrate (RBX1, E3), while Cul5 is a substrate of ROC2 (RBX2/SAG, E3) [ 41 ]. Moreover, ROC1 knockdown lead to upregulated ATF4 expression, which can promote the apoptosis of tumor cells [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…9 A, the genetic nanomedicine significantly inhibited the Neddylation modification of Cul1 but had little influence on the Neddylation modification of Cul5 in Huh7 cells. This outcome was a result of the role of Cul1 as a ROC1 substrate (RBX1, E3), while Cul5 is a substrate of ROC2 (RBX2/SAG, E3) [ 41 ]. Moreover, ROC1 knockdown lead to upregulated ATF4 expression, which can promote the apoptosis of tumor cells [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Expression of the genes encoding the NEDD8 conjugases, UBE2M and UBE2K, was significantly greater in HGSOC than in LMP (F = 5.25, p < 0.05; F = 22.81, p < 0.0001). UBE2M is a NEDD8-conjugating enzyme that facilitates neddylation and activation of Cullin Ring 1–4 ligases, while UBE2F facilitates the neddylation of Cullin Ring 5 ligases [ 59 , 60 , 61 ]. UBE2F has been promoted as a target to enhance platinum sensitivity in chemotherapy of lung cancer cells [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…RBX1 is overexpressed in many primary tumours, including liver cancer, non-musculoinvasive transitional cell carcinoma of the bladder (NMIBC), and lung cancer [32][33][34][35][36]. Several studies have shown that RBX1 is participated in different aspects of the cancer biology, and lots of RBX1 molecular functions are in accordance with its function in cancer [37][38][39]. Nonetheless, there exist no information on the RBX1 molecular mechanisms and its concrete role in TNBC.…”
Section: Discussionmentioning
confidence: 99%